Gefitinib or Erlotinib vs Chemotherapy for EGFR Mutation-Positive Lung Cancer: Individual Patient Data Meta-Analysis of Overall Survival - Chee Khoon Lee (2018)
Background: We performed an individual patient data meta-analysis to examine the impact of first-generation epidermal growth factor receptor ( EGFR ) tyrosine kinase inhibitor (TKI) therapy on overall survival (OS) in advanced non-small cell lung cancer (NSCLC). Methods: Data from trials comparing EGFR-TKI against chemotherapy in exon 19 deletion (del19) or exon 21 L858R (L858R) EGFR mutations patients were used. We performed Cox regression to obtain hazard ratios (HRs) and 95% confidence intervals (CIs). Impact of postprogression therapies was examined in exploratory analyses. All statistical tests were two-sided. Results: Six eligible trials (gefitinib = 3, erlotinib = 3) included 1231 patients; 632 received EGFR-TKI and 599 received chemotherapy. At a median 35.0 months follow-up, there were 780 deaths and 1004 progressions. There was no difference in OS between EGFR-TKI and chemotherapy (HR = 1.01, 95% CI = 0.88 to 1.17, P =  .84). There was also no difference in OS for Del19 (n = 682, HR = 0.96, 95% CI = 0.79 to 1.16, P =  .68) and L858R (n = 540, HR = 1.06, 95% CI = 0.86 to 1.32, P =  .59) subgroups ( P interaction = .47), or according to smoking status, sex, performance status, age, ethnicity, or histology. However, EGFR-TKI statistically significantly prolonged progression-free survival (PFS) overall (HR = 0.37, 95% CI = 0.32 to 0.42, P  <   .001) and in all subgroups. Following progression, 73.8% from the chemotherapy arm received EGFR-TKI, and 65.9% from the EGFR-TKI arm received chemotherapy. Nine percent from the EGFR-TKI arm received no further treatment vs 0.6% from the chemotherapy arm. Following disease progression, patients randomly assigned to EGFR-TKI had shorter OS than those randomly assigned to chemotherapy (12.8 months, 95% CI = 11.4 to 14.3, vs 19.8 months, 95% CI = 17.6 to 21.7). Conclusions: Despite statistically significant PFS benefit, there is no relative OS advantage with frontline gefitinib or erlotinib vs chemotherapy in EGFR -mutated NSCLC. This finding is likely due to the high rate of crossover at progression.